2018
DOI: 10.2147/cmar.s156566
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of treatment in Swiss cancer patients at the end-of-life

Abstract: PurposeCurrent evidence on the care-delivering process and the intensity of treatment at the end-of-life of cancer patients is limited and remains unclear. Our objective was to examine the care-delivering processes in health care during the last months of life with real-life data of Swiss cancer patients.Patients and methodsThe study population consisted of adult decedents in 2014 who were insured at Helsana Group. Data on the final cause of death were provided additionally by the Swiss Federal Statistical Off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…A recent study reported that 25.6% were still treated tumour specifically within the last 4 weeks of life and 79.1% within the last 3 months [ 10 ]. Bahler et al discovered that in their study cohort, almost 10% of patients started a new chemotherapy regimen in the last 4 weeks of life [ 8 ]. They discussed that palliative late-stage chemotherapy might be evaluated as an option to improve survival, especially in patients who are explicitly seeking further treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that 25.6% were still treated tumour specifically within the last 4 weeks of life and 79.1% within the last 3 months [ 10 ]. Bahler et al discovered that in their study cohort, almost 10% of patients started a new chemotherapy regimen in the last 4 weeks of life [ 8 ]. They discussed that palliative late-stage chemotherapy might be evaluated as an option to improve survival, especially in patients who are explicitly seeking further treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the time, the EOL phase treatment is determined by palliative and/or supportive care. But in some cases, patients and their caregivers are explicitly seeking for further treatment options mainly because they are not willing to stop active treatment phase [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, for QIs relating to clinical events, the number of cases tends to be significantly small in a small country such as Switzerland for the comparison of practices, physician networks or regions (QI. [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…The high quality of the Helsana database has been previously validated, and data were widely used to investigate the aspects of healthcare quality and several patient outcomes. [21][22][23][24] Study subjects were considered eligible for inclusion in the study if they were aged ≥18 years in 2015 and continuously covered by mandatory insurance at the Helsana Group between 1 January 2015 and 31 December 2016. Subjects living abroad, nursing home residents and patients with missing values (eg, incomplete cases) were excluded.…”
Section: Study Population and Settingmentioning
confidence: 99%
“…Recent developments in oncological therapies have offered more options to patients with advanced cancer [1,2]. However, evidence shows that patients are increasingly exposed to aggressive care at the end of life (EOL), leading to poorer outcomes, including decreased quality of life, decreased care satisfaction, more complex bereavement for survivors and increased health care utilization and costs at the EOL [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%